(untitled) (Acta Polytechnica CTU Proceedings, 2019)
Aim of this work is to study the effect of NaCl on neutron flux through graphite block. Graphite block had 39 channels drilled through it and filled with NaCl. Au and In foils and In wire was used for neutron activation measurement of the neutron flux. AmBe neutron source with nominal activity of 92.5 GBq was used. The results were compared with MCNP simulations with channels filled with salt and air. Twelve different locations for Au and In foils were used and In wires were place in three locations to measure vertical profile of neutron flux.